French-language Support for Québec's English-speaking Professionals - Juste, Catherine-Laure (Provincial Employment Roundtable (PERT), 2022)
French-language barriers can be a challenge for professionals who are English speakers and must practice their profession in accordance with French-language policies. Despite high levels of English-French bilingualism among Québec’s English speakers, French remains a challenge for some who require additional profession-specific French-language training. Not only is French-language proficiency a requirement for membership in Québec’s professional orders, but professionals who do not meet language criteria must also pass a French-language competency exam administered by the Office québécois de la langue française (OQLF). Additionally, professional orders can mandate all their members to take French-language professional competency exams throughout their careers.

Soutien en langue française pour les professionnelles et professionnels d'expression anglaise au Québec - Juste, Catherine-Laure (Provincial Employment Roundtable (PERT), 2022)
La langue française peut représenter un obstacle pour les professionnelles et professionnels d’expression anglaise qui doivent exercer leur profession en respectant les politiques linguistiques en place. Malgré un haut niveau de bilinguisme parmi les Québécois·e·s d’expression anglaise, le français demeure une embuche pour certain∙e∙s. Ces personnes professionnelles bénéficieraient de formation linguistique additionnelle en lien avec leur métier. Non seulement la maîtrise du français est un prérequis pour se joindre aux ordres professionnels québécois, mais, dans certains cas, les personnes qui ne satisfont pas aux critères linguistiques doivent aussi passer un examen de français de l’Office québécois de la langue française (OQLF). En outre, les ordres professionnels peuvent demander à leurs membres de se soumettre, durant leur carrière, à des examens de compétences linguistiques en français.

Bill 96 & Employment of English Speakers in Québec - Provincial Employment Roundtable (PERT) (2022)
On May 24, 2022, Québec’s National Assembly passed Bill 96, An Act Respecting French, the Official and Common Language of Québec. The bill, which presents significant modifications to The Charter of the French Language (Bill 101), as well as other existing legislation, was passed more than a year after it was introduced. On June 1, 2022, Bill 96 received royal assent and some of its clauses came into effect immediately. Other clauses of the bill will come into effect at later dates.

French-Language Training for the Workforce : A review of French-language training programs for the workforce in Québec - Provincial Employment Roundtable (PERT) (2022)
This report examines the status of French-language workforce programs (FLWPs) in Québec. FLWPs consist of language learning that is specifically designed to increase the integration of workers into the labour market by focusing on the vocabulary and language skills they need to improve their employability. In this report, we conducted an inventory of FLWPs that are available to French-language learners and identified the key needs, gaps and areas for improvement in the ecosystem.

Programmes de francisation de la main-d'oeuvre au Québec : Évaluation des programmes de francisation de la main-d'oeuvre québécoise - Provincial Employment Roundtable (PERT) (2022)
Le présent rapport se penche sur l’état des programmes de francisation pour la main-d’oeuvre (PFMO) au Québec. Les PFMO sont des cours de français spécifiquement conçus pour accroître l’intégration des apprenantes et apprenants de langues sur le marché du travail en étant axés sur le vocabulaire et les compétences linguistiques qui contribuent à leur employabilité. Dans ce rapport nous avons recensé les PFMO offerts aux apprenantes et apprenants de langue française, et relevé les besoins clés, les lacunes et les possibilités d’amélioration au sein de l’écosystème.